A review on family caregiving challenges in Malaysia - Chan, Siaw Leng; Matsah, Nurul Syahmah Binti; Yusuf, Aidatul Ashya Binti; Khaidir, Anis Syahmina Binti Mohd; Hamdan, Nur Haiza Binti; Kamizi, Zayti Nurallya Binti (Universitas Negeri Yogyakarta, 2022)
Family caregiving often involves family members, relatives, and partners with whom the patients have a personal relationship to assist the care. The roles of caregivers are extensive and require a lot of effort, time, and commitment. These demands might possibly affect the life of caregivers. This paper aims to identify how family caregiving in Malaysia might have jeopardized the caregiver's life. A systematic approach analysis was utilized in this study while including seventeen articles. The exclusion criteria were articles published in reputable journals containing the research topic with the keywords